HUBUNGAN KEKUATAN OTOT QUADRICEP HUBUNGAN KEKUATAN OTOT QUADRICEPS DAN POSISI PATELLA TERHADAP FUNGSI LUTUT DAN PATELLOFEMORAL PAIN SYNDROME PADA ATLET LEVEL 1 - Luh Gede Risma Yanti; Wibawa, Ari (Kinetic and Physiotherapy Comprehensive, 2024)
Introduction: Patellofemoral pain syndrome (PFPS) is a common complaint experienced by athletes, characterized by anterior knee pain around the patella. PFPS is exacerbated by physical activity, weakness in one of the quadriceps muscles, and abnormalities in the position of the patella, which contribute to the onset of PFPS and decreased knee function. This study aimed to determine whether there was a relationship between quadriceps muscle strength and patella position on knee function and PFPS in level 1 athletes. Methods: This research used the literature review method. The preparation of this study utilized secondary data from research journals that had been published and obtained from various scientific journal database sources on the internet. The search for literature articles was conducted online through searches on PubMed and Google Scholar using the keywords "Quadriceps muscle strength," "Patellofemoral Pain Syndrome," "Patella Tendon," "Knee Function," "Ultrasound," and "Patella Position." Results: The results of the five literature found that good quadriceps muscle strength can maintain knee stability and optimal patella position. The position of the patella shifts laterally, causing increased stress on the patellofemoral joint, which can interfere with knee function due to pain and increased symptoms of PFPS. The quadriceps muscle strength training program is intended to lower the incidence of PFPS. Conclusion: The study demonstrated a significant relationship between quadriceps muscle strength and knee function. It also found a notable association between patella position and knee function, with these relationships being more pronounced in individuals with PFPS than those without it.